2008
DOI: 10.1189/jlb.1008670
|View full text |Cite
|
Sign up to set email alerts
|

Age-related enlargement of lymphoid tissue and altered leukocyte composition in serglycin-deficient mice

Abstract: Serglycin (SG) is a proteoglycan that is located predominantly in the secretory granules of hematopoietic cells. Previous studies have established a crucial role for SG in promoting the storage of various secretory granule compounds that are of importance in the immune defense system. Here, we show that mice lacking SG spontaneously develop enlargement of multiple lymphoid organs, including the spleen, Peyer's patches (PP), and bronchus-associated lymphoid tissue. In the spleen, the lack of SG resulted in a si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 30 publications
2
11
0
Order By: Relevance
“…An observation in line with these findings is that aging serglycin 2/2 mice spontaneously develop a massive enlargement of multiple lymphoid tissues, including spleen, BALT, and Peyer's patches (60), suggesting that serglycin has functions in maintaining homeostasis of the body's immune cell populations, for example, through effects on proliferation, apoptosis, or both.…”
Section: Impact Of Serglycin On Immune Regulationsupporting
confidence: 59%
“…An observation in line with these findings is that aging serglycin 2/2 mice spontaneously develop a massive enlargement of multiple lymphoid tissues, including spleen, BALT, and Peyer's patches (60), suggesting that serglycin has functions in maintaining homeostasis of the body's immune cell populations, for example, through effects on proliferation, apoptosis, or both.…”
Section: Impact Of Serglycin On Immune Regulationsupporting
confidence: 59%
“…It has recently been demonstrated that animals lacking SG spontaneously develop an enlargement of multiple lymphoid tissues/organs (11) and a markedly delayed contraction of the CD8 ϩ T cell response following virus infection (12). Although multiple explanations for these findings may apply, one possibility would be that the absence of SG affects the ability of certain leukocyte populations to undergo apoptosis.…”
Section: Serglycin (Sg)mentioning
confidence: 99%
“…Flow Cytometry-Peritoneal cells (0.5 ϫ 10 6 ) were stained with a PE-conjugated CD117-specific antibody or with an isotype-matched control antibody (Immunotools, Friesoythe, Germany) as described (29) and counted on a Beckman Coulter flow cytometer.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, MC proteases possibly provide a soluble link between the innate and adaptive immunity in vivo, as demonstrated by the reduced adaptive response of mMCP-4-deficient mice in experimental arthritis (27) and by the inability of mMCP-6 deficient mice to recruit eosinophils to skeletal muscle tissue in response to infection with Trichinella spiralis larvae (28). We recently reported that SG deficiency results in several age-dependent alterations in the lymphoid system of naïve mice, possibly as a result of the impaired storage of potent inflammatory mediators within secretory granules (29). However, the importance of SGPGs for regulation of MC proteases in different inflammatory reactions is only partly understood.…”
Section: Serglycin (Sg)mentioning
confidence: 99%